2001
DOI: 10.1159/000045982
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of i-STAT Creatinine Assay

Abstract: Background: We evaluated a new, 2-min blood creatinine method using the hand-held i-STAT analyzer. Good results have already been reported using this analyzer for 10 methods including electrolytes, TCO2, pH, PCO2, bicarbonate, glucose, hemoglobin and urea for uremic blood, hemodialysate and peritoneal effluent. Methods: Evaluation included study of imprecision and accuracy. Results: Imprecision studies gave excellent results, including those for reproducibility of 6 solutions with a mean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 3 publications
0
10
0
Order By: Relevance
“…6,7 One of those studies compared concordance of i-STAT whole blood eGFR with plasma eGFR calculated from a Roche IDMS-calibrated creatinine method on a small group of patients (n = 50). This study found that sensitivity for detecting plasma eGFR less than 60 mL/min/1.73 m 2 was 100%, whereas specificity was only 85%.…”
Section: Discussionmentioning
confidence: 99%
“…6,7 One of those studies compared concordance of i-STAT whole blood eGFR with plasma eGFR calculated from a Roche IDMS-calibrated creatinine method on a small group of patients (n = 50). This study found that sensitivity for detecting plasma eGFR less than 60 mL/min/1.73 m 2 was 100%, whereas specificity was only 85%.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous portable clinical analyzers have been validated for blood gas analysis in horses using whole blood . At least 2 portable clinical analyzers have also been evaluated using peritoneal fluid in horses and people . Validation of a portable clinical analyzer using synovial fluid may be helpful to equine practitioners evaluating synovial infections in the field, because the results of these patient‐side biochemical analytes would help reinforce the clinical suspicion of synovial infection in situations where clinical laboratory support is unavailable.…”
mentioning
confidence: 99%
“…A recent review of different POCT instruments that measured creatinine also showed a wide range of biases between handheld and blood gas POCT analyzers and routine laboratory analyzers [ 12 ]. Significant proportional and absolute bias have been reported between the i-STAT hand-held analyzer and the Vitros 750 [ 13 ], Roche Cobas c702 enzymatic method [ [14] , [15] , [16] ], Beckman Synchron CX7 Jaffe method [ 17 ] and the Beckman DxC800 Jaffe assay [ 18 ]. Moreover, significant bias has been reported between the creatinine measured on Nova StatSensor and routine laboratory enzymatic methods [ 16 , [19] , [20] , [21] , [22] , [23] ].…”
Section: Discussionmentioning
confidence: 99%